Postoperative nutritional benefits of proximal parenchymal pancreatectomy for low-grade malignant lesions in the pancreatic head. Issue 11 (November 2019) - Umemoto, Kazufumi; Tsuchikawa, Takahiro; Nakamura, Toru; Okamura, Keisuke; Noji, Takehiro; Asano, Toshimichi; Nakanishi, Yoshitsugu; Tanaka, Kimitaka; Hirano, Satoshi
Abstract: Background: Outcomes of proximal parenchymal pancreatectomy (PPP) as compared to pancreatoduodenectomy (PD) have not been reported. The aim of this study was to describe the short- and long-term outcomes of patients with low-grade pancreatic head lesions who underwent PPP or PD. Methods: Patients who underwent PPP or PD for low-grade lesions between 2009 and 2017 were included. Operative factors including postoperative complications and nutritional indicators during the first-year postoperatively were compared. Results: A total of 13 and 14 patients underwent PPP and PD respectively. The PPP group demonstrated significantly less intraoperative blood loss and shorter postoperative hospital stay than the PD group. No significant differences were noted in the incidence of postoperative complications between the two groups. Nutritional indices were significantly better in the PPP group at 3 months post-surgery, but these nutritional indices were not significantly different at 6 months and 1-year. None of 12 patients who underwent PPP and did not require biliary resection developed postoperative cholangitis. None of the 12 PPP patients without preoperative diabetes developed impaired glucose tolerance after surgery. Discussion: The complication rate of PPP is equivalent to that of PD. PPP demonstrated better short-term nutritional status than PD. Moreover, preservation of the total duodenum and bile duct may reduce the risk of developing postoperative diabetes and cholangitis.